2020
DOI: 10.21106/ijma.308
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination Coverage Under the Expanded Program on Immunization in South West Cameroon

Abstract: Background: Inadequate vaccination coverage with increased risk of vaccine preventable disease outbreaks remain a problem in Africa. The aim of this study was to assess the vaccination coverage levels under the Expanded Program on Immunization (EPI) in a health area and to identify factors that affect vaccination coverage in view of providing valuable data for disease prevention. Methods: A cross-sectional household survey was conducted in August 2017 in the Mbonge health area, Southwest Cameroon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…In addition, subgroup analysis of MOV revealed different interaction patterns made up of number of contacts with health facility, education level, wealth index, and residence place. This finding matches with previous studies that found children whose mothers were educated, associated to a range of positive outcomes such as child immunisation [37]. The fact that children born to less educated mothers experienced a high risk of MOV, raises the question of mothers' knowledge of the EPI, as well as the attitude of health workers towards these mothers.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, subgroup analysis of MOV revealed different interaction patterns made up of number of contacts with health facility, education level, wealth index, and residence place. This finding matches with previous studies that found children whose mothers were educated, associated to a range of positive outcomes such as child immunisation [37]. The fact that children born to less educated mothers experienced a high risk of MOV, raises the question of mothers' knowledge of the EPI, as well as the attitude of health workers towards these mothers.…”
Section: Discussionsupporting
confidence: 89%
“…To expand childhood immunization programs, eliminate vaccine-preventable infectious diseases, and distribute vaccinations among children efficiently and universally, the WHO initiated an expanded program of immunization (EPI) in 1974 [6]. Since the initiation of the EPI program, a 29% reduction in five-year child mortality has been achieved, where an estimated 17% of under-five deaths were caused by diseases that could have been prevented by vaccinations [5,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%